2009
DOI: 10.1021/cm9000174
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Electrochemical Properties of Intermetallic PtPb Nanodendrites

Abstract: We report on a facile and environment-friendly route to synthesize intermetallic PtPb nanodendrites with controllable compositions. This involves a hydrothermal-assisted coreduction of Pt and Pb inorganic precursors by formic acid in aqueous solutions without the use of any surfactant or polymer. Our systematic structural characterization and in situ electrochemical infrared spectroscopic studies of the formed PtPb nanodendrites reveal that the underlying morphogenesis, resulting from the intermetallic phase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 47 publications
0
71
0
Order By: Relevance
“…Among them, nanoscale dendritic fractals, one type of hyperbranched structure, are of interest due to their importance connected to some fractal growth phenomena and crystallography research. A variety of dendritic nanostructures, including metals and alloys, oxides, and chalcogenides, have been synthesized by different methods, such as vapor transport technology [9], metal-organic vapor phase epitaxy [10], reverse micelles [8,11], electrochemical deposition [12], low temperature reduction method [13], surfactant-assisted synthesis [14], and hydrothermal/solvothermal synthesis [15][16][17]. Among them, solution-phase methods appear to be of particular interest because of their moderate experimental conditions for the facile scale-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, nanoscale dendritic fractals, one type of hyperbranched structure, are of interest due to their importance connected to some fractal growth phenomena and crystallography research. A variety of dendritic nanostructures, including metals and alloys, oxides, and chalcogenides, have been synthesized by different methods, such as vapor transport technology [9], metal-organic vapor phase epitaxy [10], reverse micelles [8,11], electrochemical deposition [12], low temperature reduction method [13], surfactant-assisted synthesis [14], and hydrothermal/solvothermal synthesis [15][16][17]. Among them, solution-phase methods appear to be of particular interest because of their moderate experimental conditions for the facile scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] have designed a facile hydrothermal reaction of 6 ] in aqueous solution to fabricate a-Fe 2 O 3 micron-pine dendrites, which have low Morin transition temperature. The majority of these reports have focused on cubic phase, hexagonal phase, tetragonal phase, and rhombohedral phase crystals via oriental attainment or nonequilibrium growth process [9][10][11][12][13][14][15][16][17]; however, orthorhombic phase dendritic nanostructures have seldom been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the investigations with thin films, the study with nanodendritic materials suggest that nanoparticle morphology is responsible for the significant improvement of electrocatalytic activities toward the FAO mainly because PtPbnanodendrites could expose preferential crystalline planes from the intermetallic phase evolution from a Pt-based face-centered cubic to a PtPb hexagonal [114]. With respect to the fractal dimension of the dendritic surface, an improvement of surface area could be achieved.…”
Section: Formic Acid Oxidation On Pt-pbmentioning
confidence: 99%
“…Intermetallic compounds, which are atomically ordered alloys that tend to have well-defined compositions and crystal structures that differ from those of their constituent elements, have been used as catalysts for quite some time for chemical transformations such as hydrogenation, ammonia synthesis, methanol synthesis and methanol oxidation [19]. In particular, recent work has shown that intermetallic alloys are potential candidates for catalysis in the electrochemical oxidation of small organic molecules (SOMs) because of their increased current densities and their improved resistance to CO poisoning [20][21][22][23]. Roychowdhury et al [24] prepared the ordered intermetallic compounds PtBi and PtPb using anhydrous methanol as the solvent and sodium borohydride as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%